Integrated Islamic and General Education: A Study on the Integrative Education Thought of Mohammad Natsir - Asep Herdi; Ihsan Abdurrahman (KEDJATI Foundation, 2024)
Islamic education is one of the main factors in building a nation's civilization. However, secularism has separated religious affairs from government and social affairs. It means that the teaching of Islamic education is felt only in the aspect of worshiping Allah SWT (The most glorified, the highest), known as scientific dichotomies. Besides, since the Dutch government came to Indonesia, Mohammad Natsir had paid attention to indigenous communities so that Dutch ideas regarding scientific dichotomy did not influence them by implementing integrative education. This research intended to describe the concept of Islamic education according to Mohammad Natsir and compare it with general education. This research used a qualitative approach with a literature review method. The results of the research show: (a) the concept of religious education based on monotheism as well as physical and spiritual, which cannot be separated from the sources of the Qur'an, Hadith, Creed and Morals, Fiqh Science, and the History of Islamic Culture, and (b) the integration of Islamic education with general in order to make individuals highly intellectual and religious. Therefore, this research provides an alternative source of information for developing Islamic religious education.